PENGOLAHAN IKAN BANDENG (Chanos chanos) TANPA DURI DAN STRATEGI PEMASARAN UNTUK PENINGKATAN PENJUALAN PADA KELOMPOK WANITA TANI DI DESA TAMANGAPA, KEC. MA’RANG, KAB. PANGKEP - Kasmawati Kasmawati; Hasrun Hasrun; Ernaningsih Ernaningsih; Muhammad Ikhsan Wamnebo (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
The main problem faced by the Women farmers group in Tamangapa Village, Ma'rang District, Pangkep Regency, is the inability to achieve a high selling value from processed raw materials for Bandeng fish so that they only expect the selling price of raw materials. To overcome these problems, efforts are made in the form of training, mentoring and empowerment so that partners are able to produce Milkfish with high selling value. Training and assistance in processing milkfish without thorns was held on October 12, 2021. This activity was carried out in the community meeting room of the Tamangapa mosque hall. Tamangapa Village, Marang District, Pangkep Regency. The method used is a participatory training method, which involves as many partners as possible in lectures, discussions, practices for making Bandeng Tanpa Duri, and marketing with online applications. The PkM activities of the Talaswati Peasant Women's Group in Tamangapa Village, Ma'rang District, Pangkep Regency, which we have done are running well and in accordance with the specified time. The results that have been achieved are that the group has been able to process milkfish without thorns and market it online.